Workability Investigation on the Fresh Mix of ECC Mortar and Crumb Rubber (CR)-ECC based on Variations of Palm Shell Ash, River Sand, and Cement - Lubis, Agussalim; Aswin, Muhammad; Hasibuan, Gina Cynthia R. (Syntax Literate, 2024)
Engineered cementitious composite (ECC) is a composite that has better tensile properties and behavior than concrete. ECCs are usually made of cement, water, silica sand, cementitious materials, fibers, and other additives. The term ECC mortar is used because the ECC does not use fiber. The cementitious material in this research uses palm shell ash, with a proportion of 5%, 10%, and 15% of the cement weight. As a replacement for the fiber, crumb rubbers are used, with proportions of 2.5%; 5%; 7.5%; 10% and 12.5% of the cement weight. Workability was measured based on slumpflow tests (with measurements T500 and slumpflow diameter). The objective of this study is to establish the workability of fresh mix of the ECC mortar and CR-ECC with variations in the addition of palm shell ash, cement, sand and crumb rubber. Based on the results of slumpflow tests, the average diameter for fresh ECC mortars ranges between 88 cm to 106.5 cm, and the T500 ranges from 0.28 seconds to 1.39 seconds. As for fresh CR-ECC mix, the mean slumpflow diameter is between 71 cm to 93 cm and the T500 ranging between 0.90 seconds and 1.68 seconds. All of these values meet the slumpflow requirements stipulated by EFNARC. Nevertheless, the workability of the fresh mix ECC mortar is more flowable than the fresh mix CR-ECC. This is because crumb rubbers are water-absorbing.